Kawman natu, lanuan natu solid waste management communication plan in Barangay Lamion, Bongao, Tawi-Tawi - Sali, Alyssa Fatima G. (2019)
Tawi-Tawi is a province composed of 300 islands with Bongao as its capital. It is known to be rich in marine biodiversity with fishing as one of its main sources of livelihood. Also, known as the home of the Tausugs, several residents in Tawi-Tawi live in coastal barangays. In Barangay Lamion, Bongao, there is an existing problem on solid waste management; solid waste can be found under stilt houses, floating in sea. To address this problem, the researcher developed a communication plan in using the Research-Objectives-Programming-Evaluation Process. Data was obtained by: (1) reviewing government documents, (2) distributing quantitative surveys to 266 residents of Barangay Lamion, and (3) conducting key informant interviews and a focus group discussion. The culture of the residents was also taken into consideration by the researcher, by interviewing religious leaders from the research locale. Bandura?s Self-Efficacy Theory and Roger?s Diffusion Innovation Theory were used as guides, respectively, in crafting the quantitative survey and in creating the communication plan by introducing solid waste management innovation. Results reveal that the residents have high levels of positive attitude and self-efficacy regarding solid waste management. However, they receive minimal information regarding several aspects of solid waste management. Thus, the researcher crafted a communication plan in order to address these communication gaps by proposing the use of several communication tools and the use of multiple key messages for different strands of the target audience.